(untitled) (Ameghiniana, 2013)
This paper deals with the physical characters of biogenous opaline partides, that have been found in superficial sediments from the santa fe province plains. Several animal and plant species were recognized, wich in turn correspond to identified silicic elements. Special emphasis is placed on Poriiera, Cyperaceae, Gramineae, Palmaceae and Podostemaceae. Some of the particulate opaline matter show even distribution throughout the area of study. Others are restricted to specific zones and are valuable as environment and provenance indicators